Strength and power goals for competitive rowers - McNeely, E. E.; Sandler, D.; Bamel, S. (Strength and Conditioning Journal, 2005)
This article provides strength and power goals for competitive rowers of all ages and ability. These goals will provide strength and conditioning professionals with a starting point at which to evaluate the physical preparedness of their athletes, and will help measure progress against other athletes.